ONLINE CUSTOMER EXPERIENCE FOR DIGITAL BANKING CUSTOMERS: RECONFIRMATION OF INFORMATION SYSTEM SUCCESS MODEL - Ali Maskur; Sri Nawatmi; Ignatius Hari Santoso (Journal of Management Small and Medium Enterprises (SME's))
The rapid transformation of the banking industry, driven by advancements in digital technology, has reshaped how banks deliver services and interact with customers. This study investigates the impact of system quality, information quality, and service quality on online customer experience and customer loyalty in the digital banking context. Using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, data was collected from 95 respondents who have actively used mobile banking services for over three years. The findings reveal that system quality and information quality significantly influence customer loyalty and online customer experience, while service quality does not have a direct effect on customer loyalty. Similarly, system quality does not significantly affect online customer experience unless paired with other quality dimensions. These results highlight the evolving priorities of digital banking customers, who value efficient, secure, and intuitive platforms over traditional service interactions. The study emphasizes the importance of integrating high system and information quality with personalized and responsive service to enhance the overall customer experience. This research provides theoretical and practical insights for banking institutions aiming to strengthen their digital strategies and foster sustainable customer loyalty in the competitive landscape of digital banking.